Participatory Learning with Critical Problem-Solving Approaches in Teaching Simple Machines: Its Effectiveness on Students' Science Process Skills - Ernita, Nevi; Ute, Nilawati; Sukariasih, Luh; Syarifuddin, Syarifuddin (Lensa: Jurnal Kependidikan Fisika, 2024)
This study investigates the effectiveness of participatory learning combined with a critical problem-solving approach on junior high school students' science process skills in the context of simple machines. Conducted with 61 students from Central Lombok, the research involved an experimental group (31 students) and a control group (30 students). The experimental group received participatory learning treatment with a critical problem-solving approach, while the control group was taught using traditional expository methods. The intervention included three sessions focusing on pulleys, inclined planes, and levers, each lasting 90 minutes. Students' science process skills were assessed across five aspects: preparing practical tools, assembling practical tools, reading measurements, collaborating with peers, and conveying information. The results revealed that the experimental group significantly outperformed the control group in all aspects of science process skills, with higher mean scores and lower variability. The findings indicate that participatory learning with a critical problem-solving approach is more effective than traditional methods in enhancing students' science process skills. This study's outcomes suggest that integrating interactive and student-centered approaches in science education can foster critical thinking, collaboration, and practical application of scientific concepts. The research contributes to the existing literature by demonstrating the benefits of combining participatory learning and critical problem-solving in teaching complex topics like simple machines. Future research should explore the long-term effects of these approaches and their applicability across various educational contexts and subjects.